1997
DOI: 10.1074/jbc.272.51.32141
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Conserved Cysteines in Human Tissue Inhibitor of Metalloproteinases-1

Abstract: Tissue inhibitor of metalloproteinases-1 (TIMP-1) is resistant to extremes of temperature and pH. This is thought to be due in part to the presence of six sulfhydryl bridges presumed to maintain the structural integrity of the molecule. As part of a study looking at structure-function relationships, a number of the conserved cysteine residues in TIMP-1 were targeted for replacement with serine. Single and double replacements of these conserved cysteines, as well as replacements around these cysteines, were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 40 publications
1
21
0
2
Order By: Relevance
“…We constructed a recombinant TIMP-3 protein (TIMP-3 Cys1-Ser ) that is devoid of metalloproteinaseinhibitory activity by mutating the cysteine1 residue to a serine. An analogous mutation in TIMP-1 completely abrogates metalloproteinase-inhibitory activity without affecting protein conformation (36). We used a recombinant adenovirus to overexpress the TIMP-3 Cys1-Ser mutant in rat SMC and HeLa and compared its proapoptotic activity with a previously characterized recombinant adenovirus carrying the wild type TIMP-3 gene (RAd:wtTIMP-3) or a control adenovirus (RAd:66) (19,20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We constructed a recombinant TIMP-3 protein (TIMP-3 Cys1-Ser ) that is devoid of metalloproteinaseinhibitory activity by mutating the cysteine1 residue to a serine. An analogous mutation in TIMP-1 completely abrogates metalloproteinase-inhibitory activity without affecting protein conformation (36). We used a recombinant adenovirus to overexpress the TIMP-3 Cys1-Ser mutant in rat SMC and HeLa and compared its proapoptotic activity with a previously characterized recombinant adenovirus carrying the wild type TIMP-3 gene (RAd:wtTIMP-3) or a control adenovirus (RAd:66) (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…In wild type TIMP-3 the N-terminal cysteine residue is a key to the TIMP-3-inhibitory mechanism, because it bidentally coordinates the Zn 2ϩ ion in the active site of metalloproteinases through the ␣-amino group and the peptide carbonyl group (41). An analogous TIMP-1 mutant completely lacks inhibitory activity toward MMP-1 and MMP-2, while maintaining structural integrity (36). Likewise, we demonstrated that the Cys 1 3 Ser mutation of TIMP-3 results in loss of inhibitory activity toward MMP-2.…”
Section: Timp-3-induced Apoptosismentioning
confidence: 99%
“…To determine whether this function requires MMP inhibitory activity, a TIMP-2 mutant unable to inhibit MMPs was generated. Substitution of cysteine 72 to serine (TIMP-2 C72S ) completely abrogates MMP inhibitory activity without affecting protein conformation and MMP-independent functions (Caterina et al, 1997;Bond et al, 2000). Similar to TIMP-2, expression of the mutant TIMP-2 C72S resulted in a pronounced reduction in the number of BrdU-positive cells (vector, 52 Ϯ 6.4%; TIMP-2 C72S , 9 Ϯ 2%).…”
Section: Timp-2 Inhibits Pc12 Proliferation and Regulates Expression mentioning
confidence: 99%
“…(i) The deleted amino acid sequence (residues18 -89) contains two of the major sites of interaction of TIMPs with active MMPs (6,23) (Fig. 6A), and (ii) manipulation of the corresponding region of TIMP-1 around and including Cys-70 (Cys-72 in TIMP-2) either by mutagenesis of Cys-70 (24,25) or by proteolytic cleavage at Val-68 (26) results in ablation of inhibitory activity. The construct potentially leaves intact the first 18 residues including the NH 2 -terminal sequence, which fits into active site cleft of MMPs.…”
Section: Fig 3 Regulation Of Organomercurial Activation By Timp-2mentioning
confidence: 99%